Associations between the Presence of Type 2 Diabetes and Health-Related Quality of Life (HRQoL) among US Hispanic Population - Macias, Matthew; Chang, Jongwha; Riley, Elizabeth; Park, Chanhyun; Kang, Hyeun Ah (Archives of Clinical and Biomedical Research, 2019)
Introduction: Very few studies have captured the association in health-related quality of life (HRQoL) by the presence of type 2 diabetes (T2D) among the US Hispanic population. Aim: This study was to examine the association of the presence of T2D on HRQoL measure in the US Hispanic population. Methods: This was a cross-sectional study analyzing data from the 2014-2015 Medical Expenditure Panel Survey (MEPS). This data comprised of the Hispanic population of 13,933 members (estimated population size: 36,440,400) with T2D in the US. Two multivariate regression models were used to predict HRQoL (Short Form 12) by the presence of T2D among the Hispanic population. Results: Results showed 89.1% did not have T2D condition (n=12,423), while 10.9% had T2D conditions (n=1,510). SF-12 PCS scores were 45.85 (95% CI; 44.65, 47.05) in Hispanic population with T2D and 51.23 (95 % CI; 50.77, 51.68) in Hispanic population without T2D. SF-12 MCS scores were 52.52 (95% CI; 51.98, 53.05) in patients without T2D and 49.59 (955 CI; 48.34, 50.76) in Hispanic population with T2D conditions. Conclusion: The study suggests that the presence of T2D worsens HRQoL measured by individuals' physical and mental health status among the US Hispanic population compared with non-T2D Hispanic population. Psychiatric assessment and management of T2D minority population may improve patient HRQoL.